Penerapan Platform Digital Learn and Growth Dalam Meningkatkan Kompetensi Teacherpreneurship Guru Belajar Jepara - Hamidaturrohmah; Mahendra, Danang; Saefudin, Ahmad; Nahar, Afifatun; Pratama, Adrian Dico (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Teachers wield significant influence over the quality of education. To enhance this influence, they must possess competent skills, including teacherpreneurship. This study aims to assess the efficacy of the digital learning platform,